Learning Cycle 7E with Audio Visual Media Enhancing Science Learning Outcomes - Pradipta Kencana, I Nyoman Bagus; Arini, Ni Wayan; Mahadewi, Luh Putu Putrini (International Journal of Elementary Education, 2020)
The science learning outcomes of grade V elementary school students tend to be low; this is seen from the number of students who have not reached KKM more than the number of students who have reached KKM. This is the main reason for doing this research. This study aims to determine the effect of the Learning Cycle 7E learning model providing audiovisual to the learning outcomes of science learning in fifth grade elementary school students. This type of research is a quasi-experimental study using a non-equivalent post-test only control group design. The population of this research is all of the fifth-grade elementary school students, amounting to 129 students. The sample uses a random sampling technique, with 81 students. Data collection in this study uses a test method with multiple choice test instruments. The data obtained were analyzed using descriptive statistical analysis and inferential statistics. Based on the hypothesis test obtained tcount 51.23 is greater than ttable 1.91, thus it can be concluded that there is a significant effect of the Learning Cycle 7E learning model providing audiovisual on the science learning outcomes of fifth grade elementary school students.